The mirror and the window: optical investigation of Filippo Brunelleschi (1377-1446) and Leon Battista Alberti (1404-1472) concerning “costruzione legittima” - Camelo, Midori Hijioka (Circumscribere International Journal for the History of Science, 2009)
This work attempts to identify the contributions of Filippo Brunelleschi and Leon Battista Alberti to the study of geometrical optics.